PENGARUH INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP MINAT PEMBELIAN ULANG PADA UMKM KERIPIK OPAK BERKAH DI KECAMATAN SIBIRU-BIRU - Fajar Agung Leksmana; Aprinawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of product innovation and product quality on repurchase intention at the UMKM Berkah Opak Chips in Sibiru-Biru District. This research was motivated by the low interest in purchasing Berkah Opak Chips in Sibiru-Biru District. The study sample involved 73 respondents, and data were collected using a questionnaire with 22 statements. The data analysis technique used was multiple linear regression. Based on the results, product innovation partially significantly influenced repurchase intention, with a calculated t-value of 7.365 and a significance level of 0.000. Similarly, product quality also partially significantly influenced repurchase intention, with a calculated t-value of 2.984 and a significance level of 0.004. Furthermore, product innovation and product quality simultaneously significantly influenced repurchase intention, as indicated by a calculated F-value of 84.039 and a significance level of 0.000. The coefficient of determination (R2) of 0.698 indicates that these two variables contribute 69,8% to explaining the variation in repurchase intention. Therefore, it can be concluded that product innovation and product quality significantly influence repurchase intention at the UMKM Berkah Opak Chips in Sibiru-Biru District.